Application of state space search method to find a low voltage solution for ill-conditioned system - Shahriari, Amidaddin; Mokhlis, Hazlie; Bakar, Ab Halim Abu; Karimi, Mazaher; Illias, Hazlee Azil (Przeglad Elektrotechniczny, 2012)
This paper uses the State Space Search Method (SSSM) in polar coordinate form to obtain low voltage solution and maximum loading point of ill-condition power system. SSSM improves the direction of state variables (buses voltage and phase) of system buses based on optimal multiplier to converge load flow equations in ill-conditioned system. The advantage of SSSM is apparent in constant preservation of dimension of Jacobian matrix in load flow equations. Whereas another approaches such as Homotopy and continuation power flow vary the framework of Jacobian matrix based on predictor and corrector elements during enhancing load demand. The calculation procedure of SSSM is depending on classical Newton-Raphson load flow method. The reliability of SSSM is indicated by IEEE test systems, 14 and 30 buses in well and ill-conditioned at maximum loading point as systems.